Penyuluhan Osteoporosis Kepada Masyarakat Kelurahan Kauman - Ory Kusti Oviandar; Wahyu Tri Sudaryanto; Amalia Faradilla Rahim (jurnal ABDIMAS Indonesia, 2024)
Osteoporosis is a condition marked by reduced bone mass and alterations in bone tissue microstructure, leading to increased fragility and susceptibility to fractures. Globally, 1 out of 3 women aged 50 and older, and 1 out of 5 men, will suffer from fractures related to osteoporosis. Objective: The objective of this initiative is to enhance community awareness for the prevention and mitigation of osteoporosis risk in later stages of life. Methods: The initiative involves educational sessions with counseling, utilizing PowerPoint presentations as a medium. Evaluation will be conducted through questionnaires administered both before and after the educational sessions